The Role of Parents in Caring for Children with Speech Delay: A Systematic Review - Lailatul Badriah; Yuni Sufyanti Arief; Eka Mishbahatul Mar’ah Has (Indonesian Journal of Global Health Research, 2026)
Speech delay is a developmental condition that affects children’s communication, learning, and family interactions. This condition not only impacts the cognitive and social development of affected children but also poses substantial challenges for families, particularly in caregiving, communication, and adaptation processes. This study aimed to conduct a systematic review to synthesize qualitative evidence on the roles, experiences, and challenges of parents in caring for children with speech and language delay. The review was conducted according to PRISMA guidelines. Relevant studies published between 2020 and 2025 were systematically searched in PubMed, Sage Journals, Science Direct, Scopus, Taylor and Francis databases using Boolean operators and specific keywords. The PEO framework (Population, Exposure, Outcome) guided study selection, focusing on qualitative research related to parents (such as parents, parental role, caregiving), speech delay (such as speech delay, language delay, communication disorder), and children (such as toddlers, early childhood, pediatric). The Joanna Briggs Institute (JBI) Critical Appraisal Checklist for Qualitative Research was used to assess methodological quality. Thematic synthesis revealed four overarching categories: (1) parental roles and responsibilities in providing daily stimulation, therapy practice, and advocacy; (2) challenges and burdens, including emotional stress, financial strain, and stigma; (3) coping and adaptation strategies through family support, spirituality, and personal resilience; and (4) interaction with social and service contexts, highlighting the importance of professional guidance and systemic accessibility. Parents play a central role in supporting children with speech delay, yet face significant emotional and practical challenges. Strengthening family centered care, enhancing professional parent collaboration, and reducing systemic barriers are essential.